The Effect of Administration of Centella asiatica (Pegagan) Leaf Extract on Clinical Outcomes of Adolescent Tuberculosis - Abdul Hakam; Renni Yuniati; Enrique Vicenzo Kosasih (Eduvest - Journal of Universal Studies, 2024)
Tuberculosis (TB) ranks among the top 10 causes of mortality worldwide. Indonesia stands third in Southeast Asia for the highest prevalence of TB cases. One of the adverse effects of Anti-Tuberculosis Drugs (ATD) is hepatotoxicity. Approximately 20% of patients treated with Isoniazid show elevated Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT) levels in their plasma. Despite the direct efficacy of ATD in managing TB, hepatotoxicity necessitates discontinuation of drug administration, leading to complications such as Multidrug-Resistant Tuberculosis (MDR-TB). Pegagan leaves (Centella asiatica) contain alkaloids with antibacterial properties. Extracts from Pegagan leaves have been shown to enhance expression of Cluster of Differentiation (CD)4, CD8, and macrophages. Furthermore, this extract can increase cytokine production, including Tumor Necrosis Factor-alpha (TNF-α) and Interferon-gamma (IFN-γ). Based on these premises, this study aims to investigate whether administration of Pegagan leaves extract significantly impacts levels of Hypoxia-Inducible Factor 1-alpha (HIF-1α), TNF-α, IFN-γ, Serum Glutamic Oxaloacetic Transaminase (SGOT), and Serum Glutamic Pyruvic Transaminase (SGPT) in teenage TB patients.